The Role of Higher Education Institutions in Advancing Sustainable Development - Drelich-Skulska, Bogusława; Sobocińska, Magdalena (Publishing House of Wroclaw University of Economics and Business, 2025)
This chapter examines the potential and importance of higher education institutions in promoting sustainable development. The analysis draws on Fischer’s model of critical literature review. To illustrate the role of universities in this process, the case of the Wroclaw University of Economics and Business is presented. Here, the goals of sustainable development are embedded in the university’s strategic priorities and translated into concrete actions. The discussion focuses on the drivers and areas of sustainable development implementation in higher education, including scientific research and its commercialisation, educational concepts and curricula, as well as institutional governance. Particular attention is paid to the development of competencies, especially green and cultural competencies, that universities are uniquely suited to cultivate in line with the principles of sustainability. The findings suggest that fulfilling their social mission, alongside research and teaching, enables universities not only to enhance the standard and quality of life, but also to advance the very concept of the university and its role in society.
Quote as: Drelich-Skulska, B., & Sobocińska, M. (2025). The Role of Higher Education Institutions in Advancing Sustainable Development. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 19-30). Publishing House of Wroclaw University of Economics and Business.
Keywords: higher education institutions; sustainable development; social responsibility; environmental awereness; cultural competencies